How Authoritarian Leadership Affects Employee's Helping Behavior? The Mediating Role of Rumination and Moderating Role of Psychological Ownership - Asim, Muhammad; Zhiying, Liu; Nadeem, Muhammad Athar; Ghani, Usman; Arshad, Mahwish; Yi, Xu (Frontiers in Psychology, 2021)
Interpersonal helping behaviors, i.e., voluntarily assisting colleagues for their workplace related problems, have received immense amount of scholarly attention due to their significant impacts on organizational effectiveness. Among several other factors, authoritarian leadership style could influence helping behavior within organizations. Furthermore, this relationship could be mediated by workplace stressor such as rumination, known as a critical psychological health component leading to depressive symptoms, hopelessness and pessimism. In the meantime, less research attention has devoted to probe the crucial role of psychological ownership, which can buffer the adverse effects of authoritarian leadership upon rumination. Building on conservation of resources theory, this study investigates the adverse impacts of authoritarian leadership on employees' helping behaviors through mediating role of rumination, and also examines the moderating effect of psychological ownership between the relationship of authoritarian leadership and rumination. The data were collected from 264 employees in education and banking sectors and the results show: (i) authoritarian leadership has adverse impacts on helping behavior, (ii) rumination mediates the relationship between authoritarian leadership and employees' helping behaviors, and (iii) psychological ownership moderates the positive relationship between authoritarian leadership and rumination. This study concludes that authoritarian leadership has adverse impacts upon helping behavior, which needs to be controlled/minimized. The findings are of great significance for managers, employees, and organizations in terms of policy implications. The limitations and future research directions are also discussed.